A hybrid quality function deployment and cybernetic analytic network process model for project manager selection - Mohammadi, Farahbod; Sadi, Mohammadali Kazerooni; Nateghi, Fatemeh; Abdullah, Arham; Skitmore, Martin (Journal of Civil Engineering and Management, 2014)
Identifying appropriate decision criteria and making optimal decisions in a structured way is a complex process. This paper presents an approach for doing this in the form of a hybrid Quality Function Deployment (QFD) and Cybernetic Analytic Network Process (CANP) model for project manager selection. This involves the use of QFD to translate the owner’s project management expectations into selection criteria and the CANP to weight the expectations and selection criteria. The supermatrix approach then prioritises the candidates with respect to the overall decision-making goal. A case study is used to demonstrate the use of the model in selecting a renovation project manager. This involves the development of 18 selection criteria in response to the owner’s three main expectations of time, cost and quality.